2011
DOI: 10.1007/s11130-010-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-extractable Procyanidins and Lignin are Important Factors in the Bile Acid Binding and Radical Scavenging Properties of Cell Wall Material in some Fruits

Abstract: The cell wall components and the food functions of alcohol-insoluble solids (AIS) of Chinese quince, quince, hawthorn, apple, pear and blueberry fruits were analyzed. Chinese quince contained characteristically high contents of cellulose, lignin, and non-extractable procyanidins (NEPCs). On the other hand, the quince AIS contained

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 26 publications
0
36
1
Order By: Relevance
“…Probably, the combination between non‐extractable phenolic compounds and undegradable polysaccharides may be an important factor for the mycotoxin adsorption by selected agricultural by‐products. It has been reported that fibres with associated tannins show broader functions than fibres without them . High contents of cellulose, lignin, and tannins in fruits have been found essential for bile acids binding activity, and removal of tannins from fibre resulted in a sharp decrease of this activity .…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the combination between non‐extractable phenolic compounds and undegradable polysaccharides may be an important factor for the mycotoxin adsorption by selected agricultural by‐products. It has been reported that fibres with associated tannins show broader functions than fibres without them . High contents of cellulose, lignin, and tannins in fruits have been found essential for bile acids binding activity, and removal of tannins from fibre resulted in a sharp decrease of this activity .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results constitute evidence of an appreciable presence of NEPP in plant foods and of their contribution to total polyphenol intake. (31) Quince 48 (32) Banana 980 (SD 45)* (27) Apple pomace 18 -23 (33) Cranberry pomace 1685 (34) Cocoa powder 602 (SD 13) (35) Carob pod 180 (36) Hydrolysable phenolics Onion 410 (SD 20)* (37) Black olive 14 -40 (38) Apple 78 (SD 6) (29) Medlar 0·5 -1·0 (39) Mandarin 39 -107 (40) Acerola 390 (SD 10)* (41) Cashew apple 1210 (SD 70)* † (41) Black currant pomace…”
Section: Occurrence Of Non-extractable Polyphenols In Dietsmentioning
confidence: 99%
“…Assay for total phenol content was based on reduction of the molybdenum-tungstate complex in F-C Reagent by phenols (Herald, Gadgil, & Tilley, 2012). The procedure was adapted to 96-well microplate platform (250 µL assay volume per well) with absorbance acquired at λ 765 nm using a microplate reader (Multiskan GO, Thermo Scientific, Australia) at 25°C.…”
Section: Total Polyphenol Content (Tpc)mentioning
confidence: 99%
“…However these residual solids have been found to contain a large amount of polyphenols including polymeric proanthocyanidins (PC). Some of the PCs are strongly bound to cell wall components (Hamauzu & Mizuno, 2011), and Perez-Jimenez, Elena Diaz-Rubio, and Saura-Calixto (2013) indicated that BPPs contribute 60-90% to the total polyphenol content in most fruits. These studies have emphasised the importance of including the bound (non-extractable) polyphenols in plant polyphenol analysis.…”
Section: Introductionmentioning
confidence: 99%